(untitled) (Journal of Asian Development Studies, 2021)
This paper investigates the impact of foreign capital inflows on domestic savings in Pakistan. The annual time series data has been used from the period 1972 to 2018 by applying ARDL and causality analysis. The results show that labor force participation rate, gross fixed capital formation, deposit interest rate, foreign direct investment, trade, GDP growth and foreign remittances have a positive impact on gross domestic savings in the long run but the variables of age dependency, external debt stock and net official development assistance have a negative impact on gross domestic savings. The coefficient of error correction model shows that the model is highly significant and converges towards equilibrium. The results of the Granger causality test exhibit that there is no causality between FDI, remittances, TRADE, external debt and gross domestic savings except ODA and GDS which shows the unilateral causality.